Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT). - Scholl, Hendrik P N; Moore, Anthony T; Koenekoop, Robert K; Wen, Yuquan; Fishman, Gerald A; van den Born, L Ingeborgh; Bittner, Ava; Bowles, Kristen; Fletcher, Emily C; Collison, Frederick T; Dagnelie, Gislin; Degli Eposti, Simona; et al. (PLoS One, 2015)
UNLABELLED: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eight of 18 patients (44%) showed a ≥20% increase and 4 of 18 (22%) showed a ≥40% increase in functional retinal area determined from Goldmann visual fields; 12 (67%) and 5 (28%) of 18 patients showed a ≥5 and ≥10 ETDRS letter score increase of visual acuity, respectively, in one or both eyes at two or more visits within 2 months of treatment. In two patients who underwent fMRI, a significant positive response was measured to stimuli of medium contrast, moving, pattern targets in both left and right hemispheres of the occipital cortex. There were no serious adverse events. Treatment-related adverse events were transient and the most common included headache, photophobia, nausea, vomiting, and minor biochemical abnormalities. Measuring the outer segment length of the photoreceptor layer with high-definition optical coherence tomography was highly predictive of treatment responses with responders having a significantly larger baseline outer segment thickness (11.7 ± 4.8 μm, mean ± 95% CI) than non-responders (3.5 ± 1.2 μm). This structure-function relationship suggests that treatment with QLT091001 is more likely to be efficacious if there is sufficient photoreceptor integrity. TRIAL REGISTRATION: ClinicalTrials.gov NCT01014052.
Keywords: Acyltransferases; Administration, Oral; Adult; Anticarcinogenic Agents; Cerebral Cortex; Child; cis-trans-Isomerases; Drug Dosage Calculations; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Radiography; Retinal Ganglion Cells; Retinal Neurons; Retinitis Pigmentosa; Treatment Outcome; Visual Acuity; Visual Fields; Vitamin A; Young Adult

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex